Relation of Helicobacter pylori infection and coronary heart disease. Issue 5 (May 1994) - Mendall, M. A.; Goggin, P. M.; Molineaux, N.; Levy, J.; Toosy, T.; Strachan, D.; Camm, A. J.; Northfield, T. C.
Abstract : BACKGROUND--There is evidence suggesting that early life experience may influence adult risk of coronary heart disease (CHD). Chronic bacterial infections have been associated with CHD. OBJECTIVE--To determine whether Helicobacter pylori, a childhood acquired chronic bacterial infection, is associated with an increased risk of coronary heart disease in later life. DESIGN--Case-control study controlling for potential confounding variables with an opportunistically recruited control group. SUBJECTS--111 consecutive cases with documented CHD were recruited from a cardiology clinic and 74 controls from a general practice health screening clinic. All were white men aged 45-65. METHODS--Serum was analysed for the presence of H pylori specific IgG antibodies by ELISA (98% sensitive and 94% specific for the presence of infection). RESULTS--59% of the cases and 39% of the controls were seropositive for H pylori (odds ratio 2.28, chi 2 7.35, p = 0.007). After adjustment by multiple logistic regression for age, cardiovascular risk factors, and current social class, the effect of H pylori was little altered (odds ratio 2.15, p = 0.03). Further adjustment for various features of the childhood environment known to be risk factors for H pylori infection only slightly weakened the association (odds ratio 1.9). H pylori seropositivity was not related to the level of risk factors in the control population. CONCLUSION--In this pilot study the association of adult coronary heart disease with H pylori seropositivity suggests that the early childhood environment may be important in determining the risk of CHD in adult life. The association needs confirmation in other better designed studies. If H pylori itself is responsible for the association, then this is of great potential importance as the infection is treatable.